2022
DOI: 10.3390/antibiotics11101452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Helicobacter pylori Antibiotic Resistance in Italy: A Review of the Literature

Abstract: Helicobacter pylori (H. pylori) resistance to antibiotics has increased worldwide in recent decades, especially to clarithromycin. As a result, the World Health Organization (WHO) identified clarithromycin-resistant H. pylori as a “high priority” pathogen in 2017. As international guidelines recommend empirical therapy as first-line treatment, it is crucial to know local resistance rates and history of antibiotic use to determine the most appropriate first-line antibiotic treatment. Italy is one of the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Important factors of H. pylori resistance evolution are the use of currently non-recommended regimens, such as triple clarithromycin-based therapy in regions with high (>15%) resistance to the agent [15,53], national antibiotic consumption, patient compliance and other host factors. High antibiotic consumption in Bulgaria can be associated with an increase in H. pylori resistance to all antibacterials, except tetracycline [36] (Figure 2).…”
Section: Factors For Resistance Evolutionmentioning
confidence: 99%
“…Important factors of H. pylori resistance evolution are the use of currently non-recommended regimens, such as triple clarithromycin-based therapy in regions with high (>15%) resistance to the agent [15,53], national antibiotic consumption, patient compliance and other host factors. High antibiotic consumption in Bulgaria can be associated with an increase in H. pylori resistance to all antibacterials, except tetracycline [36] (Figure 2).…”
Section: Factors For Resistance Evolutionmentioning
confidence: 99%
“…Helicobacter pylori is a Gram-negative bacteria that inhabits the gastric mucosa and is a leading cause of chronic gastritis that eventually drives gastric ulcers, duodenal ulcers, and gastric adenocarcinoma [ 51 ]. Antibiotic treatment faces an increasing antibiotic resistance to first-line antibiotics including metronidazole, amoxicillin, and/or clarithromycin [ 51 ].…”
Section: Antimicrobial Productsmentioning
confidence: 99%
“…Helicobacter pylori is a Gram-negative bacteria that inhabits the gastric mucosa and is a leading cause of chronic gastritis that eventually drives gastric ulcers, duodenal ulcers, and gastric adenocarcinoma [ 51 ]. Antibiotic treatment faces an increasing antibiotic resistance to first-line antibiotics including metronidazole, amoxicillin, and/or clarithromycin [ 51 ]. An alternative product based on Lf loaded in biomimetic hydroxyapatite nanocrystals combined with the cell free supernatant from Lactobacillus paracasei , a probiotic with beneficial effects on gut health, has been proposed as a therapeutic for Helicobacter pylori infection [ 39 ].…”
Section: Antimicrobial Productsmentioning
confidence: 99%
“…One aspect that must be considered when discussing the potential benefits of eradication therapy is the high incidence of antibiotic-resistant H. pylori strains in the general population [112]. In a recent review of the literature, Nista et al [113] observed for instance that in Italy the rate of antibiotic resistance is so high to even be worth considering clarithromycin quadruple therapy as a first-line treatment [113]. Antibiotic resistance is obviously a problem because of the difficulties it creates to eradicate infection [114], but also because patients have to then undergo multiple therapy lines, which creates problems in itself [115].…”
Section: Future Perspectivementioning
confidence: 99%